The classification of children's literature: possibilities of subcategories (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
Classification systems have been a milestone in the history of information organization and remain significant for information sorting and retrieval. However, these systems have a gap in addressing children's literature. Thus, this research aimed to apply the Fiction Dimensions criteria proposed by Pejtersen to a children's literature collection in order to propose more specific subcategories. Through an experimental process involving a collection of 100 works, Pejtersen's criteria were applied, resulting in 6 subcategories. It is worth considering that other collections can also make use of these subcategories for classification purposes.
Keywords: bibliographic classification; children's literature classification; fiction dimensions